Determinants of ICT outsourcing among the locally-owned manufacturers in Malaysia. Issue 3 (21st November 2016) - Yap, Ching Seng; Lim, Yet Mee; Jalaludin, Farah Waheeda; Lee, Teck Heang
Abstract : Purpose: This paper aims to examine the level of information and communication technology (ICT) outsourcing and its determinants in the Malaysian locally owned manufacturing firms. Drawing on the transaction cost theory and the resource-based theory, four determinants – asset specificity, uncertainty, business skills and technical skills – were hypothesized to influence ICT outsourcing. Design/methodology/approach: Data were collected using a questionnaire survey from 104 manufacturing firms listed on the Directory of Federation of Malaysian Manufacturers. Data were then analyzed using R package partial least squares path modeling. Findings: The study reveals that slightly over two-thirds (68 per cent) of the surveyed manufacturers either fully or partially outsourced their ICT services. Asset specificity and uncertainty are found to be positively related to the level of ICT outsourcing, which contradict the prediction of the transaction cost theory. On the other hand, business skills and technical skills are not significantly related to the level of ICT outsourcing, which also conflict the resource-based arguments. Research limitations/implications: The small sample size would not be able to make meaningful conclusion for the population; the small R 2 value indicates that other important determinants of ICT outsourcing were not tested in this study, and the transaction cost theory and the resource-based theory do not adequately predict the level of ICT outsourcing in the Malaysian locally owned manufacturers. Originality/value: The study serves as one of the first studies that tested the determinants of ICT outsourcing using the transaction cost theory and the resource-based theory in locally owned manufacturing firms of a developing country.